2020
DOI: 10.1186/s12885-020-07654-y
|View full text |Cite
|
Sign up to set email alerts
|

Predictive and prognostic role of tumour-infiltrating lymphocytes in breast cancer patients with different molecular subtypes: a meta-analysis

Abstract: Background Whether tumour-infiltrating lymphocytes (TILs) play different roles in different molecular subtypes of breast cancer remains unknown. Additionally, their prognostic and predictive value in different molecular subtypes of breast cancer is still controversial. The aim of our meta-analysis was to assess the prognostic and predictive value of TILs in different molecular subtypes of breast cancer by summarizing all relevant studies performing multivariate analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
74
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 44 publications
8
74
4
1
Order By: Relevance
“…In early TNBC patients treated with anthracycline-based adjuvant chemotherapy, the levels of TILs are positively correlated with a better outcome [ 45 ]. Similar results were obtained for untreated early TNBCs, showing that higher TIL densities correlated with better survival [ 46 , 47 ]. Similarly, high quantities of cytotoxic CD8+ TILs are positively associated with a longer survival of early TNBC patients [ 48 ] and better response to neoadjuvant chemotherapy [ 49 ].…”
Section: Discussionsupporting
confidence: 75%
“…In early TNBC patients treated with anthracycline-based adjuvant chemotherapy, the levels of TILs are positively correlated with a better outcome [ 45 ]. Similar results were obtained for untreated early TNBCs, showing that higher TIL densities correlated with better survival [ 46 , 47 ]. Similarly, high quantities of cytotoxic CD8+ TILs are positively associated with a longer survival of early TNBC patients [ 48 ] and better response to neoadjuvant chemotherapy [ 49 ].…”
Section: Discussionsupporting
confidence: 75%
“…While increased TILs were associated with a survival benefit in HER2-positive and TNBC, in luminal/HER2-negative tumors high TIL was a negative prognostic factor, raising the question of the role played by the immune system in these tumors. Similar results were reached by Gao et al and Waks et al, analyzing the association between pCR and survival, and TILs in HR+ BC [67,68]. Further, another issue is how achieving a pathological complete response (pCR) correlates with long-term outcome in HR+ HER2-negative BC.…”
Section: Clinical Significance Of Tumor-infiltrating Lymphocytes In Hr+ Bcsupporting
confidence: 79%
“…TILs, the foremost mononuclear immune cells infiltrating the tumor microenvironment, and are strongly associated with breast cancer prognosis 2 . In patients treated with NAC, the pooled analysis showed that high TIL levels could predict pathological response in all breast cancer subtypes and were associated with longer DFS in the TNBC and HER2 + but not the luminal‐HER2 − subtype 3,8 . Our study confirmed that a high pre‐NAC TIL level was significantly associated with higher pCR rates in the whole population regardless of molecular subtype.…”
Section: Discussionsupporting
confidence: 73%
“…The level of tumor‐infiltrating lymphocytes (TILs) is a foremost immunobiological marker and can be classified as stromal or intra‐tumoral 2 . The presence of abundant TILs is significantly correlated with superior survival in patients with human epidermal growth factor receptor 2 (HER2)–enriched or triple‐negative breast cancer (TNBC), and studies have revealed that the stromal TIL level is a better biomarker than the level of intra‐tumoral TIL 2,3 …”
Section: Introductionmentioning
confidence: 99%